A loosely-coupled scheme for the flow-induced flapping problem of two-dimensional flexible plate with strong added-mass effect. (1st December 2020) - Zhang, Lei; Zou, Shuyan; Wang, Chizhong; Sun, Jianglong
Abstract: Loosely-coupled scheme is extensively used to simulate fluid-structure interaction (FSI) problems due to its efficiency. However, it meets the numerical difficulty of instability in the strong added-mass scenario. In this paper, a loosely-coupled scheme is proposed for solving the flow-induced flapping problem of two-dimensional (2D) flexible plate with strong added-mass effect. Specifically, finite volume method is used to simulate the flow field and mode superposition method is applied to calculate the structure field. In order to avoid the added-mass induced numerical instability, governing equation of the flexible plate is modified with added mass being added to its both sides. First of all, this proposed scheme is validated through simulating hydrodynamic response of a single cantilever flexible plate in uniform flows. Then, to study the stability of the proposed scheme, the flow-induced oscillations of a cantilever flexible plate with various low mass ratios and strong added-mass effects are studied. The critical stability boundary of the flapping dynamics of a cantilever flexible plate is also presented. Finally, the proposed scheme is applied to simulate the hydrodynamic behaviors of two parallel plates in uniform flows. Two distinct flapping dynamics models (in-phase and out-of-phase oscillations) are obtained and their corresponding flow details are illustrated. Highlights: A loosely-coupled scheme is proposed for FSI problem with strong added-mass effect. Flow-induced motion of a 2D flexible plate with various low mass ratios is discussed. Two 2D flexible plates with different lateral spacings in uniform flows are studied.